2023
DOI: 10.1123/jpah.2022-0145
|View full text |Cite
|
Sign up to set email alerts
|

A Cloth Facemask Causes No Major Respiratory or Cardiovascular Perturbations During Moderate to Heavy Exercise

Abstract: Purpose: Investigate whether a cloth facemask could affect physiological and perceptual responses to exercise at distinct exercise intensities in untrained individuals. Methods: Healthy participants (n = 35; 17 men, age 30 [4] y, and 18 women, age 28 [5] y) underwent a progressive square wave test at 4 intensities: (1) 80% of ventilatory anaerobic threshold; (2) ventilatory anaerobic threshold; (3) respiratory compensation point; and (4) exercise peak (Peak) to exhaustion, 5-minute stages, with or without a tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…A study from our laboratory showed no major perturbations in respiratory and cardiovascular responses during moderate to heavy exercise in untrained adults, although face mask reduced time to exhaustion. 4 However, data are scant regarding children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A study from our laboratory showed no major perturbations in respiratory and cardiovascular responses during moderate to heavy exercise in untrained adults, although face mask reduced time to exhaustion. 4 However, data are scant regarding children.…”
mentioning
confidence: 99%
“…3 During unmitigated stages of the pandemic, this tool was shown to be useful to circumvent the spread of the disease and to prevent individuals with debilitating conditions to be infected. The adverse effects anecdotally attributed to wearing a face mask during exercise, such as extreme shortness of breath, insufficient supply of oxygen, and other hemodynamic alterations, have been consistently refuted in several populations, 4,6,9 which reinforces the safety of mask usage during exercise. Nonetheless, the concern remains that wearing a mask during exercise, particularly at higher intensities, could further deteriorate cardiorespiratory responses in groups with pre-existing health conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation